FAKTOR EKSPLOITASI JENIS MERANTI DI JAMBI, KALIMANTAN TENGAH DAN KALIMANTAN TIMUR - Sampe Radja Simarmata; Dulsalam Dulsalam (Pusat Penelitian dan Pengembangan Hasil Hutan, 1985)
The study was carried out in three locations in Jambi, Central Kalimantan and East Kalimantan. The number of forest companies observed in each location varies from 2 to 4 which were randomly selected.The study concludes that :The logging waste ranges from 16,3 % to 24,6 % of the clear bole volume. The average logging waste is 22,2 % consists of 12,2 % trimming waste and stumps, and 9 % defects.The exploitation factor ranges from 75,4 % to 83,7 % and the average is 0,80. This value was previously used for the observed locations.Diameter class has a highly significant effect (P<0,01) on exploitation factor. The exploitation factor proportionally increases with the log diameters.